1982
DOI: 10.1177/00220345820610090601
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Ultrastructural, Microradiographic, and Electron-probe Studies of an Unusual Case of Regional Odontodysplasia

Abstract: Structural, ultrastructural, microradiographic, and electron microprobe studies of an unusual case of odontodysplasia were performed. Two cusps were absent from one molar. Normal prismatic enamel and mantle dentin were present on the two others. The dentinal mass resembled osteodentin. The mineral content of enamel and dentin was decreased compared to that of the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Radiopaque areas have occasionally been noted within such radiolucencies (11,28). Rarefaction of bone and thinned trabeculae have been noted (6,34,38,82,88) although we have not personally observed this and others have eommented that the bone was nortnal (15,61,62,67).…”
Section: Ciinicai Findingsmentioning
confidence: 54%
See 2 more Smart Citations
“…Radiopaque areas have occasionally been noted within such radiolucencies (11,28). Rarefaction of bone and thinned trabeculae have been noted (6,34,38,82,88) although we have not personally observed this and others have eommented that the bone was nortnal (15,61,62,67).…”
Section: Ciinicai Findingsmentioning
confidence: 54%
“…Some authors have suggested that their cases show affeeted primary teeth without correspondingly involved permanent successors. Hindsight and a careful review of published radiographs suggests that the permanent teeth were (38). HrrcittN (34) described "unerupted deciduous (?)…”
Section: Ciinicai Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histology reports on structural, ultrastructural, microradiographic and electron probe microanalysis of the cases of odontodysplasia indicated a lack of enamel on some cusps and hypoplastic enamel on others. However, the abnormal prismatic structure and mineral content of the enamel was only slightly different when compared to normal enamel [9,10,21].…”
Section: Discussionmentioning
confidence: 99%